Perbedaan Siswi yang Anemia dan Tidak Anemia Terhadap Nilai Hasil Ujian di SMP Negeri 2 Kec. Siak Tahun 2018 - Indrayani, Siska (Menara Ilmu, 2019)
Anemia occurs when the production of hemeglobin less so levels in the blood is low. Anemia can lead to reduced power and concentration of one’s thought. Anemia impact on the decline in academic ability in school. This study aims to determine differences in students who are anemicand not anemic to the value of the exam results. The research design used was survey analytical with case control approach. The sample in this study were 50 people. The sampling technique is this research is purposive sampling. Statisticial test in this study using Mann-Whitney Test. Research results are known to students who experience of anemic with poor exam resultsas much 19 students (86,9%). While students who experience of anemic with good exam results as much 6 students (21,6%). Mann-Whitney results obtained the value p = 0,000. Based on these results can be concluded that there are differences students who are anemic and not anemic to the value of the exam results at SMP N 2 Districts of Siak 2018. Keywords: Knowledge, Ante Natal Care Visit, Primigravida